Stabilization of rigid formations with direction-only constraints - Bishop, Adrian N.; Shames, Iman; Anderson, Brian D.O. (2011 50th IEEE Conference on Decision and Control and European Control Conference, 2011)
Direction-based formation shape control for a collection of autonomous agents involves the design of distributed control laws that ensure the formation moves so that certain relative bearing constraints achieve, and maintain, some desired value. This paper looks at the design of a distributed control scheme to solve the direction-based formation shape control problem. A gradient control law is proposed based on the notion of bearing-only constrained graph rigidity and parallel drawings. This work provides an interesting and novel contrast to much of the existing work in formation control where distance-only constraints are typically maintained. A stability analysis is sketched and a number of illustrative examples are also given.